Insecticide activity of Beauveria bassiana and castor bean oil against Plutella xylostella under greenhouse (Bioscience Journal, 2013)
The diamondback moth, Plutella xylostella (L.) (Lepidoptera: Plutellidae), one of the principal pests of brassicas, can reduce productivity and thus cause losses for brassica farmers. Alternative controls, such as biological agents and plant extracts, may be used to reduce insect populations, either alone or in conjunction with pest management programs. The objective was to evaluate the insecticidal activity of Beauveria bassiana (Bals.) Vuill. and castor bean oil and mixtures of both components against the diamondback moth. To do so, we separately used castor bean oil (at 2% concentration), the isolate ESALQ-447 and a commercial formulation (Boveril® WP), and a mixture of castor bean oil with the isolate and the B. bassiana product formulation, totaling six treatments with a control. Assays were carried out under greenhouse with the respective treatments sprayed on cabbage plants infested with four second instar larvae of P. xylostella. The evaluated parameters were larval mortality and pupal and larval viability. All treatments reduced larval viability in relation to the control, however, only the ESALQ-447 isolate or a mixture of the isolate with castor bean oil reduced pupal viability, significantly reducing the pest population levels in the next generation. Castor bean oil mixed with B. bassiana, however, does not augment pest mortality.